The Personal is National: Queering the nation in Denmark and Ireland - Barrowcliffe, Liam (Culture and History: Student Research Papers, 2022)
This article analyses how those who identify as lesbian, gay or bisexual (LGB) in Denmark and the Republic of Ireland see themselves in relation to hegemonic narratives of the nation. A range of personal narratives from the two national contexts were collected and analysed as narrative texts for the ways they represented positionality, agency and belonging in the wider discourse of the nation. LGB lives are often reduced to legislative turning points in national narratives, but this study shifts the focus onto the myriad of other formative experiences that contribute to their national sense of self. While a significant body of work has focused on the intersection of LGB(TQ) and national identity as harmful, leading to theories such as homonationalism, this article sees the relationship as more nuanced, and capable of going beyond acceptance/rejection or inclusion/exclusion dichotomies.